Prevalence of Fragile X syndrome in Georgian patients with autism spectrum disorder and/or intellectual disability: cross-sectional study and review of current approaches - Tabatadze, Nazi; Koniashvili, Otar; Melikishvili, Gia; Bienvenu, Thierry; Cuisset, Laurence; Tassone, Flora; Protic, Dragana D.; Naneishvili, Nino; Zarandia, Maia; Gverdtsiteli, Sopo; Kakabadze, Sophio; Gachechiladze, Tamar; et al. (Frontiers in Pediatrics, 2025)
Fragile X syndrome (FXS) is the most common inherited form of intellectual disability (ID) and autism spectrum disorder (ASD). Despite its clinical importance, data on FXS prevalence in Georgia remains limited. This study aims to assess the prevalence of FXS in individuals with ID and/or ASD in Georgia and to review current diagnostic and management approaches. A total of 441 patients (n = 332 males and n = 109 females) diagnosed with ID and/or ASD based on DSM-5 criteria underwent genetic testing for FXS using a PCR-based approach. The FXS full mutation was identified in 25 patients (5.7%), and four individuals were carriers of the premutation. One patient had a large FMR1 deletion, thus the prevalence of the full mutation (FM) was 5.9%, and the prevalence of a premutation was 0.9%. The FXS-positive cohort showed a significant male predominance (80.77%). Among patients with ASD, 1.9% tested positive for FXS, and these individuals displayed more severe behavioral problems, requiring more intensive intervention. Phenotypic features such as a long face (76.9%), joint hypermobility (61.5%), and flat feet (53.8%) were commonly observed. The study underscores a significant diagnostic delay, with the average age of clinical ID/ASD diagnosis at 8.42 years and a lag of 4.63 years before FXS is identified. Compared to the U.S., where FXS diagnosis occurs at 35–41 months, Georgia faces significant barriers, including low awareness, lack of early screening, and limited access to genetic testing. Efforts to address these challenges include public awareness campaigns and integration of early genetic testing protocols.